Testicular swelling leading to a diagnosis of adrenocortical carcinoma – co-incidence or causation?. (21st June 2021) - Batool, Maria; Fennell, David; Slattery, David; Leen, Eamon; Cormican, Liam; Sreenan, Seamus; H McDermott, John
Abstract : Summary: Adrenocortical carcinoma (ACC) is a rare malignancy with an incidence of 0.7–2.0 cases/million/year. A majority of patients present with steroid hormone excess or abdominal mass effects, and in 15% of patients ACC is discovered incidentally. We present a case of 30-year-old otherwise asymptomatic Caucasian male who presented with a testicular swelling. Subsequent imaging and investigations revealed disseminated sarcoidosis and an 11 cm adrenal lesion. An adrenalectomy was performed. Histological examination of the resected specimen confirmed an ACC and also demonstrated a thin rim of adrenal tissue containing non-caseating granulomas, consistent with adrenal sarcoid. Learning points: This case highlights an unusual presentation of two uncommon diseases. This case also highlights how separate and potentially unrelated disease processes may occur concomitantly and the importance, therefore, of keeping an open mind when dealing with unusual diagnostic findings. We also hypothesize a potential link between the ACC and sarcoidosis in our patient.